Quality of Life Following Surgical Treatment of Post Cholecystectomy Bile Duct Injury - Joshi, Anip; Adhikari, Subodh (Journal of Nepal Health Research Council, 2019)
Background: The Roux-en-Y hepaticojejunostomy surgery provides the mainstay of treatment in cases of bile duct injury following cholecystectomy.The aim of this study is to assess the quality of life in patients who underwent surgical repair of bile duct injury following cholecystectomy.Methods: The prospective cross sectional study was conducted in Gastrointestinal Surgery Unit, Bir Hospital, National Academy of Medical Sciences. The cases of bile duct injury following cholecystectomy who underwent surgical repair from April 2013 to March 2018 were included. The data collection was done using SF-36 quality of life questionnaire tool.The study was conducted after ethical clearance from Institutional Review Board of National Academy of Medical Sciences.Results: There were 26 cases of referred bile duct injury admitted in gastrointestinal surgery department from 2013 April till 2018 March out of which 19 (73%) were included in the study.More than half of the patients had limitations in carrying out vigorous activities (as running or lifting heavy objects) and 5.2% had a lot of limitations in carrying our moderate activities (as moving a table).63.1% of the patients did not have any interference with social activities with family, friends, neighbors or social groups because of their physical health or emotional problems. Conclusions: The surgical repair of bile duct injury following laparoscopic cholecystectomy has an impact on ability to perform work or daily activities as a result of physical health. However, it has little impact on patient’s perception of general health and social activities.Keywords: Cholecystectomy; BDI; QoL.